2023
DOI: 10.3390/ijms24021382
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase System in Pathogenesis of Pulmonary Fibrosis: A Hidden Threat of COVID-19

Abstract: Pulmonary fibrosis is a common and threatening post-COVID-19 complication with poorly resolved molecular mechanisms and no established treatment. The plasminogen activator system, including urokinase (uPA) and urokinase receptor (uPAR), is involved in the pathogenesis of COVID-19 and contributes to the development of lung injury and post-COVID-19 pulmonary fibrosis, although their cellular and molecular underpinnings still remain obscure. The aim of the current study was to assess the role of uPA and uPAR in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…For the NF‐κB‐mCherry reporter plasmid, five NF‐κB response element repeats and a minimal promoter (Table ) were incorporated in the mCherry2‐C1 plasmid. Small hairpin RNA (shRNA) targeting the human CIITA gene and a scrambled shRNA sequence (Table ) were cloned into the pLKO.1 plasmid as previously described 13 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the NF‐κB‐mCherry reporter plasmid, five NF‐κB response element repeats and a minimal promoter (Table ) were incorporated in the mCherry2‐C1 plasmid. Small hairpin RNA (shRNA) targeting the human CIITA gene and a scrambled shRNA sequence (Table ) were cloned into the pLKO.1 plasmid as previously described 13 …”
Section: Methodsmentioning
confidence: 99%
“…Small hairpin RNA (shRNA) targeting the human CIITA gene and a scrambled shRNA sequence (Table S2) were cloned into the pLKO.1 plasmid as previously described. 13…”
Section: Plasmids and Cloningmentioning
confidence: 99%
“…The relationship between plasminogen activation system and acute lung injury has been vigorously discussed. At the same time, its role in COVID-19-induced PF is also being widely studied (Shmakova et al, 2023). Studies have shown that urokinase plasminogen activator (uPA) and urokinase-type plasminogen activator receptor (uPAR) are involved in the pathogenesis of COVID-19 and contribute to the development of PF through single-cell RNA-seq and immunohistochemical analysis.…”
Section: Plasminogen Activator System In Covid-19-induced Emt and Pfmentioning
confidence: 99%
“…At the end of 2019, an unprecedented outbreak of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) broke out in Wuhan, Hubei Province, China, and then spread rapidly throughout China and the world (Shmakova et al, 2023). The unprecedented spread of COVID-19 has brought great challenges and harms to global public health, and attracted the attention and response of the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation